Anticoagulant therapy for sepsis‐associated disseminated intravascular coagulation: the view from Japan. (19th June 2014) - Iba, T.; Gando, S.; Thachil, J.
Summary The current management of disseminated intravascular coagulation (DIC) is based on aggressive treatment of the underlying condition and resuscitation with appropriate blood products. Anticoagulant therapy has appeared and disappeared in the different guidelines and important documents detailing the treatment of DIC. For example, Surviving Sepsis Campaign (SSC) guidelines, the 'global standard' for the management of severe sepsis, had recombinant activated protein C highly recommended in the original version, but this was withdrawn in the latest version due to the lack of evidence. In contrast, recent international guidance released from the International Society on Thrombosis and Haemostasis has introduced the potential efficacy of other agents. In sepsis‐related DIC, the basis for anticoagulant therapy comes from the mounting evidence for the anti‐inflammatory effects which these agents possess and can prove beneficial in septic situations. Several studies have clearly shown the important cross‐talk between coagulation and inflammation in patients with sepsis. More recently, neutrophil extracellular traps and damage‐associated molecular patterns (DAMPs), especially histones, have been demonstrated to play a crucial role in the coagulopathy of sepsis. Once again, the natural anticoagulants have an important function in neutralizing the effects of DAMPs and histones. In this review, in addition to examining the important role of anticoagulants in the septic milieu, the clinical studies examining antithrombin, recombinant thrombomodulin and plasma‐derived activated protein C are detailed. However, large‐scale randomized controlled trials are yet to be performed, with important consideration of the timing, dosage and duration of treatment.